Rape as a weapon of war in eastern DRC and its impact on survivors' marital satisfaction - Honnête Nyandu Kasali (International Journal of Studies in Psychology)
Rape in armed conflict is a major issue in the Democratic Republic of Congo (DRC), where it is used as a weapon of war to dismantle social structures and inflict long-term trauma on survivors. This study examines the impact of rape on survivors' marital satisfaction, highlighting the differences between wartime rape and intimate or community-based sexual violence. The methodology employs a quantitative approach with a sample of 201 rape survivors from the South Kivu and North Kivu provinces. Data were collected using the Marital Satisfaction Inventory (MSI) and analyzed through statistical tests (ANOVA, t-tests). Contrary to initial expectations, the results indicate that rape committed by armed actors has a lesser impact on marital satisfaction than rape perpetrated by intimate partners or community members. The study also identifies key factors contributing to marital distress, such as repeated assaults, the time elapsed since the last incident, and the public disclosure of the rape. Finally, the findings highlight the importance of psychosocial support in improving survivors' resilience and strengthening post-trauma marital dynamics. These results underscore the need for targeted approaches in the care and protection of victims.